2018
DOI: 10.7197/223.vi.412273
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Contribution of (18)F-FDG PET/CT Scan in Cancer of Unknown Primary

Abstract: The aim of the present study was to evaluate the clinically diagnostic contribution of 18 Ffluorodeoxyglucose positron emission tomography combined with computed tomography (18 F-FDG PET/CT) in patients with cancer of unknown primary (CUP). Method: The retrospective investigation, cross-sectional analysis of 124 18 F-FDG PET/CT scans of patients with CUP between June 2014 and July 2015 was performed. The increased 18 F-FDG uptake focus were assessed in correlation with histopathology. The diagnostic accuracy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Previous studies had indicated that the most frequently identified primaries in CUP by 18F-FDG PET/CT were lungs or head and neck carcinoma [14,15], as the results of our study. 18F-FDG PET/CT has proven its usefulness in localizing a primary tumor in the head-neck area compared to contrast-enhanced CT and MRI and could be recommended as an early diagnostic modality in the workup of these patients [16,17].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies had indicated that the most frequently identified primaries in CUP by 18F-FDG PET/CT were lungs or head and neck carcinoma [14,15], as the results of our study. 18F-FDG PET/CT has proven its usefulness in localizing a primary tumor in the head-neck area compared to contrast-enhanced CT and MRI and could be recommended as an early diagnostic modality in the workup of these patients [16,17].…”
Section: Discussionsupporting
confidence: 86%